In vitro detection of marine invertebrate stem cells: utilizing molecular and cellular biology techniques and exploring markers - Mohajer, Fatemeh; Khoradmehr, Arezoo; Riazalhosseini, Behnaz; Zendehboudi, Tuba; Nabipour, Iraj; Baghban, Neda (Frontiers in Cell and Developmental Biology, 2024)
Marine invertebrate stem cells (MISCs) represent a distinct category of pluripotent and totipotent cells with remarkable abilities for self-renewal and differentiation into multiple germ layers, akin to their vertebrate counterparts. These unique cells persist throughout an organism's adult life and have been observed in various adult marine invertebrate phyla. MISCs play crucial roles in numerous biological processes, including developmental biology phenomena specific to marine invertebrates, such as senescence, delayed senescence, whole-body regeneration, and asexual reproduction. Furthermore, they serve as valuable models for studying stem cell biology. Despite their significance, information about MISCs remains scarce and scattered in the scientific literature. In this review, we have carefully collected and summarized valuable information about MISC detection by perusing the articles that study and detect MISCs in various marine invertebrate organisms. The review begins by defining MISCs and highlighting their unique features compared to vertebrates. It then discusses the common markers for MISC detection and in vitro techniques employed in invertebrate and vertebrates investigation. This comprehensive review provides researchers and scientists with a cohesive and succinct overview of MISC characteristics, detection methods, and associated biological phenomena in marine invertebrate organisms. We aim to offer a valuable resource to researchers and scientists interested in marine invertebrate stem cells, fostering a better understanding of their broader implications in biology. With ongoing advancements in scientific techniques and the continued exploration of marine invertebrate species, we anticipate that further discoveries will expand our knowledge of MISCs and their broader implications in biology.